Whole‐Exome Sequencing Reveals Overlap Between Macrophage Activation Syndrome in Systemic Juvenile Idiopathic Arthritis and Familial Hemophagocytic Lymphohistiocytosis. Issue 12 (December 2014) - Kaufman, Kenneth M.; Linghu, Bolan; Szustakowski, Joseph D.; Husami, Ammar; Yang, Fan; Zhang, Kejian; Filipovich, Alexandra H.; Fall, Ndate; Harley, John B.; Nirmala, N. R.; Grom, Alexei A.
<x xml:space="preserve">Abstract</x> Objective Macrophage activation syndrome (MAS), a life‐threatening complication of systemic juvenile idiopathic arthritis (JIA), resembles familial hemophagocytic lymphohistiocytosis (HLH), a constellation of autosomal‐recessive immune disorders resulting from deficiency in cytolytic pathway proteins. We undertook this study to test our hypothesis that MAS predisposition in systemic JIA could be attributed to rare gene sequence variants affecting the cytotolytic pathway. Methods Whole‐exome sequencing was used in 14 patients with systemic JIA and MAS and in their parents to identify protein‐altering single‐nucleotide polymorphisms/indels in known HLH‐associated genes. To discover new candidate genes, the entire whole‐exome sequencing data were filtered to identify protein‐altering, rare recessive homozygous, compound heterozygous, and de novo variants with the potential to affect the cytolytic pathway. Results Heterozygous protein‐altering rare variants in the known genes (LYST, MUNC13‐4, and STXBP2) were found in 5 of 14 patients with systemic JIA and MAS (35.7%). This was in contrast to only 4 variants in 4 of 29 patients with systemic JIA without MAS (13.8%). Homozygosity and compound heterozygosity analysis applied to the entire whole‐exome sequencing data in systemic JIA/MAS revealed 3 recessive pairs in 3 genes and compound heterozygotes in 73 genes. We also identified 20 heterozygous rare protein‐altering variants that occurred in at least 2 patients. Many of the identified genes encoded proteins with a role in actin and microtubule reorganization and vesicle‐mediated transport. "Cellular assembly and organization" was the top cellular function category based on Ingenuity Pathways Analysis (P < 3.10 × 10−5). Conclusion Whole‐exome sequencing performed in patients with systemic JIA and MAS identified rare protein‐altering variants in known HLH‐associated genes as well as in new candidate genes.